AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI KASUS PENGELOLAAN DANA DESA PEMOGAN KECAMATAN DENPASAR SELATAN TAHUN ANGGARAN 2016) - Wismayanti Kadek Wiwin Dwi; Purnamaningsih Putu Eka (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2018)
Implementation of the principle of accountability of Village Fund management starting from the planning stage, implementation of all activities, and after the activities of village fund management is expected to be accountable. Judging from the object and method of analysis used, this research is included in qualitative descriptive research. This type of research seeks to describe the real picture of the phenomena that occur in the management of village funds, especially accountability of village fund management pemogan district of South Denpasar. To dissect this issue of Financial Accountability Theory, there are two indicators used in this study including: (a) Transparency Indicators proven by the absence of open village governance attitude towards village fund management from planning, implementation and accountability stages, (b) Indicators of Accountability (Accountability) evidenced by the different amounts of village funds used in reports on village financial accountability and reports on the use of village funds owned by BPMPD Kota Denpasar and Accountability Report of APBDes Pemogan Village caused by budget changes in October and accountability report with evidence of fund usage still not synchronized.